Planning and managing public relations campaigns : a strategic approach - Gregory, Anne, 1953- (London ; Kogan Page, 2008)
"Getting a public relations campaign or program off the ground can seem an overwhelming task. But, as with any project, the secret of success lies in good planning and effective management. This fully updated fourth edition of Planning and Managing Public Relations Campaigns provides a revised and more dynamic 12-step planning model to help all practitioners implement and run a campaign. With new coverage of key social media developments and using new case studies, Anne Gregory covers vital topics including: the role of PR in organizations; the importance of context; research and analysis; communication theory; setting objectives; publics and content; strategy and tactics; timescales and resources; evaluation and review. "--
"Getting a public relations campaign or programme off the ground can seem overwhelming. Planning and Managing Public Relations Campaigns provides a blueprint for all practitioners. Practical and easy to read, the book presents a 12-point plan for ensuring success of campaigns of all sizes, covering many vital areas including the role of public relations in organizations, the importance of context, research and analysis, setting objectives, strategy and tactics, timescales and resources, evaluation and review. Planning and Managing Public Relations Campaigns is widely regarded as one of the best 'how-to' guides for students and practitioners. This fully updated fourth edition features new developments in public relations, including social media, along with new case studies including WRAP's Love Food, Hate Waste campaign; The Sleep Pod Hotel Media Tour; McArthur River Mining; AkzoNobel's Corporate Revolution; the UK Department of Culture, Media & Sport's First World War Centenary Commemorations; and Lanson's campaign for unbiased.co.uk. About the PR in Practice series: Published in collaboration with the Chartered Institute of Public Relations (CIPR), the PR in Practice series consists of accessible, practical introductions to day-to-day public relations practice and management issues. The series' action-oriented approach keeps practitioners' knowledge and skills up to date"--
Keywords: Public relations; Management; Public relations -- Great Britain; BUSINESS & ECONOMICS / Public Relations; BUSINESS & ECONOMICS / Advertising & Promotion; BUSINESS & ECONOMICS / Marketing / General